Bacterial Filtration Efficiency - Stevina, Lany; Tjampakasari, Conny Riana (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2024)
Background: The specifications of medical masks are different from those of non-medical masks although they may appear similar. Currently, the Indonesian Government through the Ministry of Health has made efforts to tighten supervision of the quality of medical mask products circulating in the community. Bacterial Filtration Efficiency (BFE) testing is one of the requirements for medical masks to obtain circulation permit from the Indonesian Ministry of Health. Medical masks can be considered good if they have a minimum bacterial filtration efficiency of 95%. If the percentage of BFE result is greater, then the ability of the mask to filter bacteria is also greater. This review aims to provide information on the performance of various types of medical masks through BFE testing and the relationship with the characteristics of the materials used. Method: Relevant articles were obtained from PubMed, Science Direct, Research Gate, Google Scholar, and springer databases and then filtered. Sixteen articles were reviewed and included in this study to achieve the study objective. Result: There are various types of medical masks including surgical masks and N-95 respirator masks. One of the requirements for medical masks is the ability to filter or (BFE) test. Factors that affect the filtration ability of masks include the type of material used and the method of making the mask. Conclusion: Testing the filtration efficiency of medical masks can be done through the Bacterial Filtration Efficiency (BFE) test. Good medical masks must have a minimum bacterial filtration efficiency of 95%.